XML and the semantic web it's time to stop squabbling-they're not incompatible. - Hendler, James (XML journal :the ultimate enterprise resource.)
Over the past couple of years the Semantic Web bandwagon has really started rolling. Publications ranging from the popular press to the top scientific journals have printed excited articles claiming the potential of the Semantic Web as exceeding that of the Web itself. In this article we'll explain what the Semantic Web is all about and, perhaps more important, attempt to dispel a pervasive myth-that XML and the Semantic Web are somehow incompatible.